Does Good Corporate Governance Able to Moderate The Relationship of Financial Performance Towards Firm Value? - Setiawanta, Yulita (AKRUAL: Jurnal Akuntansi, 2019)
This study aims to find out explicitly whether good corporate governance is able to moderate the relationship between financial performance and firm value that occurs in companies listed on the Indonesian stock exchange. Research was conducted on food and beverage companies in 2008 - 2017. The 10-year observation period obtained 50 observational data. By using Warppls 6.0 in processing observational data, the results show that financial performance has an influence on the value of the company. This research also proves that good corporate governance proxied by share ownership by company leaders is able to positively moderate the effect of financial performance on firm value, but not for institutional share ownership. In this case it can be said that the greater the dominance of the owner in corporate governance, the more positive the opportunity to obtain financial performance and the firm value becomes easier to achieve.